ダイ 26 ジ ナンキョク チイキ カンソク タイ エットウ タイ ホウコク 1985-1986 - 福西, 浩; フクニシ, ヒロシ; Fukunishi, Hiroshi (1987)
P(論文) 第26次日本南極地域観測隊越冬隊員35名は1985年1月より1986年1月までの1年間, 昭和基地とみずほ基地を中心とした地域で, 極光, 地磁気, 電離層, 気象, 地震, 潮汐, 測地の定常観測を例年どおり実施するとともに, 各種研究観測を実施した。研究観測では, MAP(中層大気国際共同観測計画)の一環として極域中層大気の総合観測(4年計画最終年次)を昭和基地で大規模に実施するとともに, IAGP(国際南極雪氷計画)の一環として内陸部では「東クィーンモードランド地域雪氷・地学研究計画(7年計画の4年次)」を実施した。このほか「環境モニタリング」と「ヒトの生理学的研究」を継続実施した。本報告では, それら多種多様な定常・研究観測の概要と, それを支えた設営部門の活動を紹介する。 The wintering party of the 26th Japanese Antarctic Research Expedition composed of 35 personnel carried out routine observations and research activities at Syowa and Mizuho Stations, along the coast of Lutzow-Holm Bay and in the dome area of East Queen Maud Land from January 1985 to January 1986. The main research activity at Syowa Station was a coordinated observation of the polar middle atmosphere, which was performed as part of the International Middle Atmosphere Program (MAP). The middle atmosphere in the altitude range of 10-120km was observed by a combination of remote sensing techniques from the ground and spacecraft and in situ measurements by 9 balloons and 13 rockets. The remote-sensing facilities operated on the ground were ruby and dye laser radars, VHF doppler radar, multi-beam riometer and auroral TV cameras. In addition to the MAP activities at Syowa Station, survey trips for environmental research were carried out at short intervals along the coast of Lutzow-Holm Bay. Glaciological and meteorological studies were carried out, as part of the International Antarctic Glaciological Project (IAGP), at Mizuho Station (70.7°S, 44.3°E), Advanced Camp (74.2°S and 35.0°E), Dome Camp (77.0°S and 35.0°E), and on the traverse routes. The 200-m ice-core drilling was completed at Advanced Camp. The top of the East Queen Maud Land dome was discovered to be located at 77°22′24″S and 39°36′50″E with the altitude of 3807m above sea level. departmental bulletin paper